Cavity in the Loop - Scheunert, David; Gehrunger, Jonas; Hochberger, Christian; Lens, Dieter; Klingbeil, Harald (SC24-W: Workshops of the International Conference for High Performance Computing, Networking, Storage and Analysis, 2024)
Particle accelerators are physically and technically complex systems. Their operation requires demanding beam control systems. To support the development of new components in a beam phase control system for a synchrotron, we present a CGRA-based hardware/software environment that is capable of simulating the fundamental beam behaviour, leading to a hardware-in-the-loop setup. We show that this setup is able to emulate the longitudinal phase oscillations of the particle bunches in real-time.